Digital competences in pedagogy, citizenship and professional development of the university professorship - Derling José Mendoza Velazco; María Andreina Salvatierra Choez; María Eulalia Briones Ponce; Iris María Sánchez Azúa; Fabián Gustavo Menéndez Menéndez (Universidad de Guadalajara, 2024)
In today's digitized world, digital competences are required to facilitate the transition to the Internet. For professorship, these competences go beyond knowledge of a particular subject. They focus on the skills needed to transmit that knowledge to students. A quantitative approach study was applied. The design was non-experimental and descriptive. The population and sample correspond to the 70 teachers who worked in the Faculty of Humanistic and Social Sciences during the first semester of 2023. The instrument for data collection was a teaching self-assessment. The competencies in digital citizenship showed the highest levels of teacher mastery with a value of 5. The competencies in pedagogy and professional development showed a value of 4. 93% of UTM-CHS teachers stated they had participated in training activities on the use of ICT in education. In conclusion, university faculty in Ecuador must have a stronger digital academic background; they must establish better pedagogical and professional development skills, research capacity, knowledge of educational technologies, intercultural skills and leadership skills. To ensure a high-quality learning environment all three areas must be at the same level of outcomes. For that, university professional development leads to establishing good pedagogy. Then pedagogy is strengthened through digital citizenship.